Method for preparing multilevel structure silicon-carbon lithium ion battery composite negative electrode material by single carbon source one-step method
The preparation of multi-stage structure silicon-carbon composite anode material by a single carbon source method solves the mechanical problems and poor conductivity caused by volume effects of silicon-based lithium-ion batteries, and realizes a stable conductive network and efficient lithium ion migration, which improves the electrochemical performance and cycle life of the battery.
Patent Information
- Application Number
- CN202510391845.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2025-07-08
AI Technical Summary
The existing silicon-based lithium-ion battery anode materials have mechanical problems and unstable solid electrolyte interfaces due to volume effects during the alloying/dealloyation process. The traditional synthesis method has complex processes, high costs, and unstable multi-stage structure, which affects the battery cycle life and rate performance.
A single carbon source method is used to prepare a multi-stage structure silicon-carbon composite anode material, and a carbon cladding layer and a two-dimensional carbon nanosheet frame are formed on the surface of silicon particles through chitosan. The carbon structure is reconstructed at low temperature and high temperature using a metal chloride inducer to form a stable conductive carbon network, buffer volume expansion and improve conductivity.
The synthesis process is simplified, production costs are reduced, electrochemical reaction capacity and battery cycle life are improved, the conductivity of electrode materials and lithium ion migration channels are enhanced, and the lithium storage capacity of the battery is improved.
Smart Images

Figure CN120280471A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of anode materials for lithium-ion batteries, and particularly relates to a method for preparing a multi-level structured silicon-carbon composite anode material for lithium-ion batteries by a one-step method using a single carbon source. Background Art
[0002] With the acceleration of the decarbonization of the global energy industry, the demand for higher-capacity energy storage devices for applications such as electric vehicles is increasing day by day. Silicon (Si) can undergo an alloying reaction at room temperature to store lithium to form Li 15 Si4, with a theoretical capacity as high as 3579 mA h g -1 , which is ten times that of the theoretical specific capacity of commercial graphite anode materials (372 mAh g -1 ), and is considered to be one of the most promising high-capacity anode materials. However, Si expands and contracts sharply during the alloying / dealloying process, causing a huge volume effect (>300%), leading to mechanical problems and an unstable solid electrolyte interface (SEI). With the progress of charge and discharge cycles, the mechanical fracture and pulverization of Si particles result in the continuous destruction and regeneration of the SEI film, accelerating the decomposition of the electrolyte and the aggregation of irreversible lithium ions, thereby reducing the battery cycle life and even the disintegration of the entire electrode. In addition, due to the inherently low intrinsic conductivity and slow reaction kinetics of the material, the rate performance of the Si anode is also affected.
[0003] In order to overcome the above disadvantages and realize the commercial application of silicon-based anodes, related research has proposed combining carbon coatings (such as pitch, glucose, dopamine, etc.) with other carbon-based conductive materials (such as carbon nanotubes, carbon nanosheets, and graphene, etc.) to construct a hierarchical structure and form a stable protective layer, which can not only adapt to the volume change of the electrode material but also maintain the integrity of the conductive network. At present, the method of constructing a hierarchical structure often uses more than two carbon sources and constructs a multi-level structure in batches. Therefore, the traditional synthesis method has defects such as complex process, high production cost, and unstable multi-level structure, which greatly limits the performance of its lithium storage capacity. Summary of the Invention
[0004] Aiming at the problems in the production of existing silicon-carbon anode materials, such as long process, complex carbon source, poor composite effect, etc., and the problems of particle pulverization, low conductivity, high first irreversible capacity, etc. caused by the volume effect of silicon-based materials; the present invention provides a method for preparing a multi-level structured silicon-carbon lithium battery composite anode material by a one-step method using a single carbon source, which has the advantages of simple process, controllable composite structure, green and pollution-free, etc.
[0005] The object of the present invention is achieved through the following steps: (1) Dissolve chitosan uniformly in an acetic acid solution, and then add an inducer, where the mass ratio of chitosan to the inducer is 1:2 to 1:6, and mix and stir for 0.5 to 3 h; after complete dissolution, add silicon powder to the above mixture and disperse it by ultrasonic treatment to obtain a precursor mixture, where the ratio of silicon powder to chitosan is 1:1 to 1:3, and ultrasonic for 0.5 to 3 h; (2) Freeze-dry the precursor mixture obtained in step (1), where the drying time is 36 to 72 h and the drying temperature is -60 to -10°C; after complete drying, place it in a tube furnace and sinter it under an argon / nitrogen atmosphere to obtain a silicon-carbon composite material precursor (Si@C / C / MCl x , M = Na, Zn, Li, etc.), and heat it to 700 to 1200°C at a heating rate of 2 to 5°C min -1 and react for 1 h to 4 h; (3) The silicon-carbon composite material precursor (Si@C / C / MCl x , M = Na, Zn, Li, etc.) obtained in step (2) is washed with deionized water for multiple times to remove the inducer, filtered, and dried in a vacuum oven to obtain a multi-structured silicon-carbon lithium battery composite anode material (Si@C / C).
[0006] The inducer in step (1) includes but is not limited to one or more of metal chlorides such as sodium chloride, zinc chloride, and lithium chloride.
[0007] In step (3), for the Si@C / C / MCl x precursor, the range of x is 0 to 2.
[0008] The beneficial effects of the present invention: After the chitosan of the present invention is carbonized, a carbon coating layer is formed on the surface of silicon particles and a two-dimensional carbon nanosheet framework is formed in-situ. Among them, a thin carbon layer with a uniform thickness is coated on the surface of silicon particles through a simple carbonization process. At the same time, under the action of an inducer (metal chlorides such as NaCl, ZnCl2, LiCl, etc.), the chitosan undergoes structural reconstruction to form a carbon structure framework. At low temperatures, the chitosan forms a linear structure carbon framework through simple aggregation, while at high temperatures, the chitosan undergoes structural reconstruction after carbonization to form a two-dimensional carbon nanosheet conductive carbon network. The silicon particles are firmly in-situ on the two-dimensional carbon nanosheet framework, forming a multi-level structure silicon-carbon composite material (Si@C / C) with amorphous carbon coating and structural carbon composite. On the one hand, the carbon material can provide a buffer space for Si, accommodate volume expansion to a certain extent, thereby effectively reducing the cracking and pulverization of silicon during the alloying / dealloying process. At the same time, the excess carbon material forms a stable and uniform two-dimensional carbon nanosheet conductive carbon network under the induction of sodium chloride, providing more diffusion channels for the migration of lithium ions between material particles, and improving the conductivity of the electrode material, thereby enhancing the electro-chemical reaction ability. On the other hand, this preparation method can effectively solve problems such as long process, complex carbon source, and poor composite effect in the production of silicon-carbon anode materials.
[0009] The present invention not only realizes the effective coating of providing a firm and stable conductive coating on the surface of silicon particles, but also can construct a stable two-dimensional carbon skeleton, which is of great significance for the practical application of silicon as an anode material for lithium-ion batteries while reducing the production cost of silicon-based materials and simplifying the synthesis process. Brief Description of the Drawings
[0010] Figure 1 It is a thermogravimetric comparison diagram of the multi-level structure silicon-carbon lithium-ion battery composite anode material prepared by the one-step method with a single carbon source under different sintering temperatures in Examples 1-4 of the present invention; Figure 2 It is a scanning electron microscope image of the multi-level structure silicon-carbon lithium-ion battery composite anode material prepared by the one-step method with a single carbon source in Example 2 of the present invention; Figure 3 It is a transmission electron microscope image of the multi-level structure silicon-carbon lithium-ion battery composite anode material prepared by the one-step method with a single carbon source in Example 2 of the present invention; Figure 4 It is a charge-discharge rate comparison diagram of the multi-level structure silicon-carbon lithium-ion battery composite anode material prepared by the one-step method with a single carbon source in Examples 1-4 of the present invention; Figure 5 It is a charge-discharge platform curve diagram of the multi-level structure silicon-carbon lithium-ion battery composite anode material prepared by the one-step method with a single carbon source in Example 3 of the present invention; Figure 6 It is a charge-discharge platform curve diagram of the multi-level structure silicon-carbon lithium-ion battery composite anode material prepared by the one-step method with a single carbon source in Example 4 of the present invention; Figure 7 It is the cycle performance diagram of the multi - structure silicon - carbon lithium - ion battery composite anode material prepared by the one - step method with a single carbon source in Example 5 of the present invention. Detailed implementation manners
[0011] The present invention will be further described in detail below with reference to the drawings and embodiments, but the protection scope of the present invention is not limited to the content described.
[0012] Example 1 (1) Chitosan was uniformly dissolved in acetic acid solution, and then the inducer sodium chloride was added. The mass ratio of chitosan to sodium chloride was 1:2, and the mixture was stirred for 0.5 h. After complete dissolution, silicon powder was added to the above - mentioned mixture and ultrasonically dispersed to obtain a precursor mixture. The mass ratio of silicon powder to chitosan was 1:2, and ultrasonic treatment was carried out for 1 h. (2) The precursor mixture obtained in step (1) was freeze - dried, with a drying time of 48 h and a drying temperature of - 57°C. After complete drying, it was placed in a tube furnace and sintered in an argon / nitrogen atmosphere to obtain a silicon - carbon composite material precursor (Si@C / C / NaCl) at a heating rate of 5 °C / min -1 , heated to 800°C, and the reaction time was 4 h. (3) The silicon - carbon composite material precursor (Si@C / C / NaCl) obtained in step (2) was washed with deionized water for multiple times to remove the inducer, filtered, and dried in a vacuum oven to obtain a multi - structure silicon - carbon lithium - battery composite anode material (Si@C / C - 800).
[0013] The thermogravimetric curve of the multi - structure silicon - carbon lithium - ion battery composite anode material prepared in this example is as Figure 1 shown. It can be seen from the figure that as the temperature increases, the carbon content of the sample gradually decreases and the silicon content increases.
[0014] Weigh 0.070 g of the composite material prepared in this example, 0.015 g of acetylene black, and 0.015 g of sodium alginate (SA), put them into a mortar, mix and grind for 20 min, then add 2 mL of deionized water, and continue to grind for 30 min. The viscous mixture was evenly coated on copper foil, then preliminarily dried at 80°C for 15 min, and then dried in a vacuum oven at 80°C for 12 h. After that, the copper foil was rolled, and then cut into circular pieces with a diameter of 14 mm to prepare the electrode sheet.
[0015] In a glove box filled with argon (O2 content < 1 ppm, water content < 1 ppm), the electrode sheet, separator, lithium sheet, and nickel foam mesh were assembled into a button - type battery in a conventional method, and the battery electrochemical performance was tested on a constant - current charge - discharge system. The rate - cycling result diagram is as Figure 4As shown, it can be seen from the figure that at current densities of 0.2, 0.5, 1, 2, and 3 A g -1 the multi - structured silicon - carbon lithium - battery composite anode material prepared by the one - step method with a single carbon source exhibits excellent rate performance, and its discharge specific capacities are 1682, 1339, 1192, 1006, and 744 mAh g -1 respectively.
[0016] Example 2 (1) Chitosan was uniformly dissolved in acetic acid solution, and then inducer sodium chloride was added. The mass ratio of chitosan to sodium chloride was 1:2, and the mixture was stirred for 0.5 h. After complete dissolution, silicon powder was added to the above - mentioned mixture and ultrasonicated for 1 h. The mass ratio of silicon powder to chitosan was 1:2, and the ultrasonic treatment lasted for 1 h, obtaining a precursor mixture. (2) The precursor mixture obtained in step (1) was freeze - dried for 48 h at a drying temperature of - 57°C. After complete drying, it was placed in a tubular furnace and sintered in an argon / nitrogen atmosphere to obtain a silicon - carbon composite material precursor (Si@C / C / NaCl) at a heating rate of 5 °C min -1 , heated to 900°C, and the reaction time was 4 h. (3) The silicon - carbon composite material precursor (Si@C / C / NaCl) obtained in step (2) was washed with deionized water multiple times to remove the inducer, filtered, and dried in a vacuum oven to obtain a multi - structured silicon - carbon lithium - battery composite anode material (Si@C / C - 900).
[0017] The scanning electron microscope and transmission electron microscope of the multi - structured silicon - carbon lithium - battery composite anode material prepared by the one - step method with a single carbon source in this example are as shown in Figure 2 and Figure 3 . It can be clearly observed that a hierarchical structure can be clearly seen. After the carbonization of chitosan, a thin carbon layer (Si@C) is first formed on the surface of Si particles. Through the induction of NaCl, a relatively uniform and stable two - dimensional carbon nanosheet conductive carbon network is formed between Si@C particles. Si@C is uniformly filled between the two - dimensional carbon nanosheet conductive carbon networks, and finally a multi - structured silicon - carbon composite material (Si@C / C) is formed.
[0018] Weigh 0.070 g of the composite material prepared in this example, 0.015 g of acetylene black, and 0.015 g of sodium alginate (SA), put them into a mortar, mix and grind for 20 min, then add 2 mL of deionized water and continue to grind for 30 min. The viscous mixture is uniformly coated on a copper foil, then preliminarily dried at 80°C for 15 min, and then dried in a vacuum oven at 80°C for 12 h. After that, the copper foil is rolled and cut into circular pieces with a diameter of 14 mm to prepare the electrode.
[0019] In a glove box filled with argon (O2 content < 1 ppm, water content < 1 ppm), the electrode sheet, separator, lithium sheet, and nickel foam mesh were assembled into a coin cell by a conventional method, and the battery electrochemical performance was tested on a constant current charge-discharge system. The rate cycling result graph is as Figure 4 shown. It can be seen from the figure that at current densities of 0.2, 0.5, 1, 2, and 3 A g -1 , the composite anode material for multi-structured silicon-carbon lithium batteries prepared by the one-step method with a single carbon source exhibits excellent rate performance, and its discharge specific capacities are 2150, 1579, 1412, 1185, and 912 mAh g -1 of discharge specific capacity.
[0020] Example 3 (1) Chitosan was uniformly dissolved in an acetic acid solution, and then the inducer sodium chloride was added. The mass ratio of chitosan to sodium chloride was 1:2, and the mixture was stirred for 0.5 h. After complete dissolution, silicon powder was added to the above mixture and ultrasonicated for dispersion to obtain a precursor mixture, where the mass ratio of silicon powder to chitosan was 1:2, and ultrasonicated for 1 h; (2) The precursor mixture obtained in step (1) was freeze-dried, with a drying time of 48 h and a drying temperature of -57 °C. After complete drying, it was placed in a tube furnace and sintered in an argon / nitrogen atmosphere to obtain a silicon-carbon composite material precursor (Si@C / C / NaCl) at a heating rate of 5 °C min -1 , heated to 1000 °C, and the reaction time was 4 h; (3) The silicon-carbon composite material precursor (Si@C / C / NaCl) obtained in step (2) was washed with deionized water multiple times to remove the inducer, filtered, and dried in a vacuum oven to obtain a composite anode material for multi-structured silicon-carbon lithium batteries (Si@C / C-1000).
[0021] Weigh 0.070 g of the composite material prepared in this example, 0.015 g of acetylene black, and 0.015 g of sodium alginate (SA), put them into a mortar, mix and grind for 20 min, then add 2 mL of deionized water and continue to grind for 30 min. The viscous mixture was evenly coated on the copper foil, then preliminarily dried at 80 °C for 15 min, and then dried in a vacuum oven at 80 °C for 12 h. After that, the copper foil was rolled and cut into a circular piece with a diameter of 14 mm to prepare the electrode sheet.
[0022] In a glove box filled with argon (O2 content < 1 ppm, water content < 1 ppm), the electrode sheet, separator, lithium sheet, and nickel foam mesh were assembled into a coin cell by a conventional method, and the battery electrochemical performance was tested on a constant current charge-discharge system. The charge platform curve is as Figure 5As shown, it can be seen from the figure that the material prepared in this example exhibits excellent lithium storage capacity as the anode material of a lithium-ion battery. At a current density of 1 A g -1 The discharge specific capacities after 1, 50, 100, 150, and 200 cycles are 1250, 969, 740, 240, and 90 mAh / g respectively. After 150 cycles, the capacity decay is relatively large, possibly due to the volume effect during cycling, which leads to cracking and pulverization of the electrode, thereby causing a large capacity loss.
[0023] Example 4 (1) Chitosan was uniformly dissolved in an acetic acid solution, and then the inducer sodium chloride was added. The mass ratio of chitosan to sodium chloride was 1:2, and the mixture was stirred for 0.5 h. After complete dissolution, silicon powder was added to the above mixture and ultrasonically dispersed to obtain a precursor mixture. The mass ratio of silicon powder to chitosan was 1:2, and ultrasonic treatment was carried out for 1 h. (2) The precursor mixture obtained in step (1) was freeze-dried for 48 h at a drying temperature of -57°C. After complete drying, it was placed in a tube furnace and sintered in an argon / nitrogen atmosphere to obtain a silicon-carbon composite material precursor (Si@C / C / NaCl) at a heating rate of 5 °C min -1 , heated to 1100°C, and the reaction time was 4 h. (3) The silicon-carbon composite material precursor (Si@C / C / NaCl) obtained in step (2) was washed with deionized water multiple times to remove the inducer, filtered, and dried in a vacuum oven to obtain a multi-structured silicon-carbon lithium battery composite anode material (Si@C / C-1100).
[0024] Weigh 0.070 g of the composite material prepared in this example, 0.015 g of acetylene black, and 0.015 g of sodium alginate (SA), put them into a mortar, mix and grind for 20 min, then add 2 mL of deionized water and continue to grind for 30 min. The viscous mixture was evenly coated on copper foil, then preliminarily dried at 80°C for 15 min, and then dried in a vacuum oven at 80°C for 12 h. After that, the copper foil was rolled and cut into circular pieces with a diameter of 14 mm to prepare the electrode.
[0025] In a glove box filled with argon (O2 content < 1 ppm, water content < 1 ppm), the electrode, separator, lithium sheet, and nickel foam mesh were assembled into a button battery in a conventional method, and the battery electrochemical performance was tested on a constant current charge-discharge system. The charge platform curve is as Figure 6 As shown, it can be seen from the figure that the material prepared in this example exhibits good lithium storage capacity as the anode material of a lithium-ion battery. At a current density of 1 A g -1At a current density, the discharge specific capacities after 1, 50, 100, 150, and 200 cycles are 1272, 948, 760, 614, and 323 mAh g respectively -1 .
[0026] Example 5 (1) Chitosan was uniformly dissolved in acetic acid solution, and then inducer sodium chloride was added. The mass ratio of chitosan to sodium chloride was 1:6, and the mixture was stirred for 0.5 h; after complete dissolution, silicon powder was added to the above mixture and ultrasonicated for dispersion to obtain a precursor mixture. The mass ratio of silicon powder to chitosan was 1:2, and ultrasonic treatment was carried out for 1 h; (2) The precursor mixture obtained in step (1) was freeze-dried, with a drying time of 48 h and a drying temperature of -57 °C; after complete drying, it was placed in a tubular furnace and sintered under an argon / nitrogen atmosphere to obtain a silicon-carbon composite precursor (Si@C / C / NaCl). The heating rate was 5 °C min -1 , and the temperature was raised to 900 °C, with a reaction time of 4 h; (3) The silicon-carbon composite precursor (Si@C / C / NaCl) obtained in step (2) was washed with deionized water for multiple times to remove the inducer, filtered, and dried in a vacuum oven to obtain a multi-structured silicon-carbon lithium battery composite anode material (Si@C / C - 600%).
[0027] Weigh 0.070 g of the composite material prepared in this example, 0.015 g of acetylene black, and 0.015 g of sodium alginate (SA), put them into a mortar, mix and grind for 20 min, then add 2 mL of deionized water and continue to grind for 30 min. The viscous mixture was evenly coated on copper foil, then preliminarily dried at 80 °C for 15 min, and then dried in a vacuum oven at 80 °C for 12 h. After that, the copper foil was rolled and cut into circular pieces with a diameter of 14 mm to prepare electrode sheets.
[0028] In a glove box filled with argon (O2 content < 1 ppm, water content < 1 ppm), the electrode sheet, separator, lithium sheet, and nickel foam mesh were assembled into a button cell in a conventional method, and the electrochemical performance of the battery was tested on a constant current charge-discharge system. The result graph of the rate cycle is as Figure 7 shown. It can be seen from the figure that the material prepared in this example shows good cycle stability as the anode material of a lithium-ion battery. At a current density of 0.5 A g -1 , after 50 cycles, the capacity retention rate is 89.5%.
[0029] Example 6 (1) Dissolve chitosan uniformly in acetic acid solution, and then add inducer sodium chloride, where the mass ratio of chitosan to lithium chloride is 1:2, and mix and stir for 0.5 h; after complete dissolution, add silicon powder to the above mixture and disperse it by ultrasonic treatment to obtain a precursor mixture, where the mass ratio of silicon powder to chitosan is 1:2, and ultrasonic treatment for 1 h; (2) Freeze-dry the precursor mixture obtained in step (1), where the drying time is 48 h and the drying temperature is -57 °C; after complete drying, place it in a tube furnace and sinter it in an argon / nitrogen atmosphere to obtain a silicon-carbon composite material precursor (Si@C / C / LiCl), at a heating rate of 5 °C min -1 , heat up to 900 °C, and the reaction time is 4 h; (3) The silicon-carbon composite material precursor (Si@C / C / LiCl) obtained in step (2) is washed with deionized water for multiple times to remove the inducer, filtered, and dried in a vacuum oven to obtain a multi-structured silicon-carbon lithium battery composite anode material (Si@C / C).
[0030] The specific embodiments of the present invention have been described in detail above in conjunction with the accompanying drawings. However, the present invention is not limited to the above embodiments. Within the scope of knowledge possessed by those of ordinary skill in the art, various changes can be made without departing from the gist of the present invention.
Claims
1. A method for preparing a multi - hierarchical structure silicon - carbon composite anode material for lithium - ion batteries by a one - step method using a single carbon source, characterized in that, It includes the following steps: (1) Uniformly dissolve chitosan in an acetic acid solution, and then add an inducer, where the mass ratio of chitosan to the inducer is 1:2 to 1:8, and mix and stir for 0.5 to 3 h; after complete dissolution, add silicon powder to the above mixture and disperse it by ultrasonic wave to obtain a precursor mixture; the mass ratio of silicon powder to chitosan is 1:1 to 1:3, and ultrasonic wave for 0.5 to 3 h; (2) Freeze-dry the precursor mixture obtained in step (1), where the drying time is 36 to 72 h and the drying temperature is -60 to -10 °C; After complete drying, place it in a tube furnace and sinter it under an argon / nitrogen atmosphere to obtain a silicon-carbon composite precursor. At a heating rate of 2-5 °C min -1 Heat it to 700-1200 °C and react for 1 h-4 h; (3) The silicon-carbon composite material precursor obtained in step (2) is washed with deionized water for multiple times to remove the inducer, filtered, and dried in a vacuum oven to obtain a multi-level structured silicon-carbon lithium battery composite negative electrode material.
2. The method for preparing the multi - level structure silicon - carbon lithium - ion battery composite anode material by a one - step method with a single carbon source according to claim 1, wherein: The inducer in step (1) includes one or more of sodium chloride, zinc chloride, and lithium chloride.
3. A multi-level structured silicon-carbon lithium ion battery composite negative electrode material prepared by the method according to claims 1-2.
Citation Information
Cited By
Silicon / carbon composite negative electrode material with dual carbon structure and preparation method of silicon / carbon composite negative electrode material
CN122177774A